Оцінка точності та відповідності результатів цифрового моделювання на основі даних SRTM (на прикладі території Чернівецької області) - Гуцул, Тарас; Hutsul, Taras (Видавництво Львівської політехніки, 2019)
Досліджено відповідність даних глобальних висот SRTM різним за масштабами та умовами рельєфу (рівнинний, горбкуватий, гірський) топографічним картам. Виявлено основні причини похибок та встановлено шляхи їх мінімізації. В результаті виконаного дослідження з’ясовано пропозиції по використанню ЦМР на основі джерела даних SRTM.

The purpose of the research is to evaluate the possibility of using constructed DEMs from open global altitudinal data models for applied needs by establishing their accuracy within test sections of topographic surfaces of various detail (1:25000, 1:50000, 1:100000) and terrain conditions (flat, hilly, mountain). Research methods – experimental modeling of surfaces, their statistical and spatial-correlation analysis. Comparison, analysis and evaluation of the results obtained. The correspondence of SRTM and ASTER GDEM data to different scales and conditions of topographic maps was investigated. The main causes of errors were identified and ways to minimize them were identified. Based on the study, recommendations were developed on the use of DMR based on global altitude data.
Assessment of accuracy and consistency of digital simulation results based on SRTM data (for example, Chernivtsi region)
Keywords: ГІС; ДЗЗ; модель; поверхня; рельєф; ЦММ; ЦМР; GIS; remote sensing; model; surface; relief; DEM; DTM; [528.422; 528.88](477.85)